(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Dietary supplement use has become increasingly common among fitness enthusiasts worldwide. Supplements, including protein, creatine, multivitamins, and omega-3 fatty acids, are often consumed to enhance muscle mass, improve performance, accelerate recovery, and support overall health. Despite their widespread use, limited data exist on the prevalence, patterns, and perceptions of supplement use among recreational gym-goers, particularly in developing countries. Objective: This study aimed to evaluate the prevalence, types, and patterns of dietary supplement use among fitness enthusiasts, assess gender differences in usage, and explore participants’ sources of information and perceptions regarding the safety and efficacy of these products. Methods: A descriptive cross-sectional study was conducted among 200 fitness enthusiasts aged 18–40 years attending selected urban gyms. Participants were recruited using convenience sampling. Data were collected through a structured, self-administered questionnaire covering sociodemographic characteristics, exercise patterns, supplement use, motivations, and sources of information. Descriptive statistics, including frequencies and percentages, were used to summarize the data. Associations between supplement use and demographic variables were analyzed using chi-square tests, with p < 0.05 considered statistically significant. Results: Among the participants, 72% reported using at least one dietary supplement. Protein supplements were most commonly consumed (55%), followed by multivitamins (35%), creatine (30%), omega-3 fatty acids (22.5%), and fat burners (15%). Gym trainers (40%) and social media platforms (35%) were the primary sources of information, while only 15% consulted healthcare professionals. Male participants were significantly more likely to use protein and creatine than females (p < 0.05). Motivations for supplement use included muscle building (60%), performance enhancement (50%), and general health maintenance (35%). Conclusion: Dietary supplement use is highly prevalent among fitness enthusiasts, with protein supplementation being the most common. Reliance on informal sources of information, gender-specific usage patterns, and limited awareness regarding safety and dosing highlight the need for targeted nutrition education and professional guidance. Regulatory oversight and evidence-based interventions are recommended to promote safe and effective supplement use in gym settings.